N-3 PUFA deposition and esterification patterns drive aroma profile remodeling in the longissimus dorsi of pigs fed flaxseed oil - Yingsen Liu; Longzhu Zhou; Luxi Lin; Shijie Wang; Yiyu Yin; Haoyang Han; Huihui Tian; Miaomiao Dong; Pingyang Li; Youyou Yang; Xiaohui Feng; Weihai Xing; et al. (Food Chemistry, 2026)

Unveiling precursor-derived PFAS burdens in landfill leachate: TOP assay reveals ultrashort-chain PFAS and DTRO removal limitations across 11 Chinese cities - Ying Zhang; Nemin Luo; Bin Yan; Lei Wang; Haolong Zhang; Mingyuan Lin; Ting Fang; Zhenchang Zhong; Huiyan Cheng; Yan Lin (Journal of Environmental Sciences, 2026)

Social Comparison Influences the Spreads of Positive and Negative Information About Opponents and Corresponding ERP Responses - Huiyan Lin; Jiafeng Liang (Brain Topography, 2026)

Functional characterization of TNF receptor-associated factor 7 in immune response and apoptotic regulation in Nile tilapia (Oreochromis niloticus) - Huaqing Sun; Chaoli He; Yujie Wang; Huiyan Lin; Lu Zhang; Xiaonuan Li; Xintong Zhen; Siwei Li; Jianmin Ye; Bingxi Li (Aquaculture, 2026)

Serum copper-zinc and copper-selenium ratios in relation to bone health among U.S. adolescents - Yanfang Shen; Haobiao Liu; Yuwen Shangguan; Qingsong Li; Xuefeng Yu; Huiyan Tang; Xue Lin (Journal of Trace Elements in Medicine and Biology, 2025)

Regulatory mechanisms of exogenous GA3 application and identification of key genes related to salt tolerance in Populus davidiana × P. bolleana - Fangyu Lin; Qi Jiang; Hu Sun; Yucheng Wang; Huiyan Guo (Trees, 2025)

Facilitating renewable natural gas production for a circular bioeconomy: AI-Driven process visualization and data augmentation on biochar-mediated anaerobic digestion - Xiaoman He; Jingyuan Guo; Xihui Kang; Xue Ning; Huichao Chen; Daolun Liang; Chen Deng; Zutan Li; Dekui Shen; Huiyan Zhang; Richen Lin; Jerry D. Murphy (Chemical Engineering Journal, 2025)

Assessing Normalized Difference Vegetation Index as a proxy of urban greenspace exposure - Yang Ju; Iryna Dronova; Qin Ma; Jian Lin; Mika R. Moran; Nelson Gouveia; Hong Hu; Haiwei Yin; Huiyan Shang (Urban Forestry & Urban Greening, 2024)

Integrating metagenomics and metabolomics to study the response of microbiota in black soil degradation - Jia Yang; Jianhu He; Lin Jia; Huiyan Gu (Science of The Total Environment, 2023)

MYB transcription factors and their roles in the male reproductive development of flowering plants - Yijie Wang; Huiyan Zhou; Yuanrong He; Xiuping Shen; Sue Lin; Li Huang (Plant Science, 2023)

Capsular polysaccharide mediates Streptococcus agalactiae to resist Nile tilapia macrophage phagocytosis - Yanjian Yang; Meng Chen; Zhelin Wu; Defeng Zhang; Huiyan Lin; Xiayi Wei; Biao Han; Zheng Guo; Jianmin Ye (Aquaculture, 2023)

Overexpression of uracil permease and nucleoside transporter from Bacillus amyloliquefaciens improves cytidine production in Escherichia coli - Ruoshuang Ma; Haitian Fang; Huiyan Liu; Lin Pan; Hongyan Wang; Heng Zhang (Biotechnology Letters, 2021)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

A versatile and efficient markerless gene disruption system for A cidithiobacillus thiooxidans : application for characterizing a copper tolerance related multicopper oxidase gene - Qing Wen; Xiangmei Liu; Huiyan Wang; Jianqun Lin (Environmental Microbiology, 2014)
Summary The acidophilic bioleaching bacteria can usually survive in high concentrations of copper ions because of their special living environment. However, little is known about the copper homeostatic mechanisms of A cidithiobacillus thiooxidans , an important member of bioleaching bacteria. Here, a putative multicopper oxidase gene ( cueO ) was detected from the draft genome of A . thiooxidans ATCC 19377. The transcriptional level of cueO in response to 10 mM CuSO 4 was upregulated 25.01 ± 2.59 folds. The response of P cueO to copper was also detected and might be stimulated by a putative CueR protein. Then, by using the counter‐selectable marker lacZ and enhancing the expression of endonuclease I ‐ SceI with tac promoter, a modified markerless gene disruption system was developed and the cueO gene disruption mutant (Δ cueO ) of A . thiooxidans was successfully constructed with a markedly improved second homologous recombination frequency of 0.28 ± 0.048. The Δ cueO mutant was more sensitive to external copper and nearly completely lost the phenoloxidase activity; however, the activity could be restored after complementing the cueO gene. All results suggest the close relation of cueO gene to copper tolerance in A . thiooxidans . In addition, the developed efficient markerless gene knockout method can also be introduced into other A cidithiobacillus strains.